(Invited) Optimized HfO2-Based MIM Module Fabrication for Emerging Memory Applications. (3rd July 2019) - Mahadevaiah, Mamathamba Kalishettyhalli; Lisker, Marco; Fraschke, Mirko; Marschmeyer, Steffen; Schmidt, Detlef; Wenger, Christian; Perez, Eduardo; Mai, Andreas
Abstract : In this work we have investigated the influence of three different fabrication approaches on the electrical behavior of HfO2 -based MIM stacks which are most popularly used in RRAM technologies. Two specific MIM layouts are analyzed to verify the electrical performance of the devices. The electrical characterization of the MIM devices are performed on wafer-scale and the characteristics of the devices are compared in terms of leakage currents, breakdown voltages, capacitances and Q-factors. Additionally, the RRAM switching behavior is investigated in terms of forming, reset and set process steps.